Legal Analysis of the Settlement of Credit Agreement Defaults Through the Small Claims Court Mechanism: A Study of Boyolali District Court Decision Number 1/Pdt.G.S/2026/PN BYL - Olivia Tiara Sejati; Burham Pranawa; Dwi Imroatus Sholikah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the resolution of credit agreement breaches through the Small Claims Court mechanism and to examine the judge's legal reasoning in Decision of the Boyolali District Court Number 1/Pdt.G.S/2026/PN BYL. The research employed a normative juridical method using statutory and case approaches. Data were collected through library research on legislation, legal doctrines, and court decisions and were analyzed qualitatively. The findings indicate that the Small Claims Court mechanism fulfills the principles of simple, speedy, and low-cost justice for resolving credit agreement disputes that satisfy the requirements of Supreme Court Regulation Number 4 of 2019. The judge's considerations were based on the existence of a legal relationship, the debtor's failure to perform contractual obligations, and the fulfillment of the elements of breach of contract under Article 1243 of the Indonesian Civil Code. The study concludes that the effectiveness of the Small Claims Court depends on the proper application of legal norms and careful judicial assessment of evidence to ensure legal certainty, justice, and legal benefit in civil dispute resolution).